2021
DOI: 10.3390/insects12070609
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Low Temperature Exposure Affects Egg Hatching of the Colorado Potato Beetle and Emergence of Overwintering Adults

Abstract: The Colorado potato beetle is a serious pest of Solanaceae in China. In early summer, cold spells in later spring may occur for brief periods in the field environmental conditions, and temperatures often deviate far below the normal temperature for short periods, such as sudden short-term low temperature, may affect the development of Colorado potato beetle eggs. This paper studies the effects of low temperature stress at 8 °C for 0 d, 1 d, 3 d, 5 d, 7 d, and 10 d on the development of Colorado potato beetle e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This shows that repeated short-term high temperature is not conducive to the hatching of CPB eggs, previous studies also have found that short-term high temperature is not conducive to the hatching of CPB eggs. CPB eggs are treated at 35 °C for 8 h and the mortality rate is 31%, and the mortality rate is 100% under the continuous high temperature of 35 °C [ 25 , 26 ]. It has been also found that the emergence rate of CPB larvae was gradually decreased with the increasing of temperature [ 23 ], and in the 35~41 °C temperature range, the CPB survival rate decreased slowly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that repeated short-term high temperature is not conducive to the hatching of CPB eggs, previous studies also have found that short-term high temperature is not conducive to the hatching of CPB eggs. CPB eggs are treated at 35 °C for 8 h and the mortality rate is 31%, and the mortality rate is 100% under the continuous high temperature of 35 °C [ 25 , 26 ]. It has been also found that the emergence rate of CPB larvae was gradually decreased with the increasing of temperature [ 23 ], and in the 35~41 °C temperature range, the CPB survival rate decreased slowly.…”
Section: Discussionmentioning
confidence: 99%
“…The eggs laid by the outdoor adults develop into the adults is the second generation adults. Collect the eggs laid by the second generation adults for the experiment [ 25 ].…”
Section: Methodsmentioning
confidence: 99%